2002
DOI: 10.1002/hed.10090
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on clinical care pathway length of stay after complex head and neck resection

Abstract: The CCP-reported performance improvement achieved by this pathway suggests improved resource use, and improved patient outcomes are achieved for postoperative care of head and neck surgery patients. Our experience suggests that advancing age creates a clinically significant increase in resource use represented by our finding of increasing LOS. This finding warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…The study selection flow diagram is summarized in Figure . Nine studies examined the implementation of a CCP using a before and after study design, however, only 1 study provided a temporal control . The remaining study used a cross‐sectional methodology .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study selection flow diagram is summarized in Figure . Nine studies examined the implementation of a CCP using a before and after study design, however, only 1 study provided a temporal control . The remaining study used a cross‐sectional methodology .…”
Section: Resultsmentioning
confidence: 99%
“…To date, the extent to which CCPs succeed in achieving this potential for better outcomes and increased efficiency of care for patients undergoing head and neck cancer surgery remains uncertain, as few studies have been done to verify their impact. The purpose of this article was to systematically assess the benefits and pitfalls of CCPs through a review of their application for head and neck cancer surgery.…”
Section: Introductionmentioning
confidence: 99%
“…6 Although the influence of many clinical factors on LOS is both intuitive and supported by data, studies from medical and elective surgical patients confirm the additional importance of nonclinical factors. [7][8][9][10][11][12] One of these factors is insurance or payer status. We hypothesized that nonclinical factors, specifically payer status, would similarly affect LOS in injured patients.…”
mentioning
confidence: 99%
“…Other authors have reported on CPWs for head and neck cancer without microvascular free flap reconstruction and will not be reviewed here. [19][20][21]46,[48][49][50][51][52][53][54] To our knowledge, the most similar study to ours is by Dautremont et al, 22 who report on a CPW for patients undergoing head and neck microvascular reconstruction. In their study, patients were admitted to the ICU postoperatively, sedated, and on ventilatory support and were then transferred to the head and neck ward after extubation.…”
Section: Discussionmentioning
confidence: 53%
“…Comparing our results to this national benchmark, we observed that our control group outcomes were similar to these, yet after implementation of the pathway, our LOS was reduced to roughly half, with a lower rate of reoperation, no need for mechanical ventilation, and a 0% pneumonia rate. Other authors have reported on CPWs for head and neck cancer without microvascular free flap reconstruction and will not be reviewed here . To our knowledge, the most similar study to ours is by Dautremont et al, who report on a CPW for patients undergoing head and neck microvascular reconstruction.…”
Section: Discussionmentioning
confidence: 68%